2013
DOI: 10.1080/02791072.2013.785811
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Drug Misuse and Risk Behaviors Among Young Injection Drug Users

Abstract: Prescription drug misuse among young adults, especially opioids, is a substantial public health problem in the United States. Although risks associated with injection of illicit drugs are well established, injection and sexual risks associated with misuse of prescription drugs are under-studied. Forty young injection drug users aged 16 to 25 who reported injection of a prescription drug were recruited in 2008–09 in Los Angeles and New York City. Descriptive quantitative and qualitative data were analyzed to il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 48 publications
(55 reference statements)
6
33
0
Order By: Relevance
“…In some occasions there is explicit forethought to use prescription drugs (mainly opioids and tranquilizers) for the purposes of engaging sexually with other men and maximizing sexual pleasure. In this process, some found that prescription opioids negatively affect their desire to have sex, which is similar to previous study of opioid users (Johnson et al, 2013). Furthermore, some participants used opioids to ease the pain associated with receptive anal sex.…”
Section: Discussionsupporting
confidence: 87%
“…In some occasions there is explicit forethought to use prescription drugs (mainly opioids and tranquilizers) for the purposes of engaging sexually with other men and maximizing sexual pleasure. In this process, some found that prescription opioids negatively affect their desire to have sex, which is similar to previous study of opioid users (Johnson et al, 2013). Furthermore, some participants used opioids to ease the pain associated with receptive anal sex.…”
Section: Discussionsupporting
confidence: 87%
“…Research conducted with heroin users has consistently shown that new injectors (generally in the 16–30 year-old age range) have especially high rates of risky injection-related behaviors (Thorpe et al, 2002; Garfein et al, 2007). Recent research documents similar patterns among injecting PO misusers (Surratt, Kurtz and Cicero, 2011; Lankenau et al, 2012; Johnson et al, 2013). Behaviors such as sharing syringes and other drug-injection equipment, use of shooting galleries and communal sharing of drug solution in group-injection situations have been well-documented among young heroin injection initiates and may place them at high risk for HIV and/or HCV transmission (Fuller et al, 2003; Goldsamt, Harocopos, Kobrak, Jost & Clatts, 2010; Harocopos, Goldsamt, Kobrak, Jost & Clatts, 2009; Guarino, Moore, Marsch & Florio, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…(2) Illicit opioid use contributes to medical morbidity, promotes risky behaviors, and complicates treatment for medical and mental health conditions. (35) In 2009, the annual societal costs of heroin and prescription opioid misuse, including overdose deaths, lost productivity, criminal justice costs, and individual health care costs, totaled an estimated $55.7 billion. (6, 7)…”
Section: Introductionmentioning
confidence: 99%